Pengembangan E-Learning berbasis Moodle pada Mata Pelajaran Pendidikan Agama Hindu dan Budi Pekerti untuk Meningkatkan Hasil Belajar Kelas VIII Semester Ganjil Tahun Pelajaran 2024/2025 di SMP Negeri 1 Ubud - I Wayan Eka Santika Putra; Ni Komang Sutriyanti; Dewa Ayu Hendrawathy Putri (JAPAM (Jurnal Pendidikan Agama), 2025)
The purpose of this study was to 1) analyze the design of e-learning development in the subject ofHindu Religious and Moral Education class VIII odd semester of the 2024/2025 academic year atSMP Negeri 1 Ubud, 2) analyze the quality of e-learning validation results developed according toexpert reviews and product trials in the subject of Hindu Religious and Moral Education class VIIIodd semester of the 2024/2025 academic year at SMP Negeri 1 Ubud, and 3) assess the effectivenessof e-learning developed on the learning outcomes of Hindu Religious and Moral Education subjectfor class VIII students in the odd semester of the 2024/2025 academic year at SMP Negeri 1 Ubud.The research method used is Research and Development with the ADDIE research model. The resultsof the media expert validation feasibility test received a score of 92% with Very Feasiblequalifications. The results of the feasibility test from the Hindu Religious Education teacher as amaterial expert were 81.43% with Very Feasible qualifications. The results of the individualeffectiveness test involving 3 students received a score of 18.520 with high effectivenessqualifications. Small group test results get a value of 25.492 with high effectiveness qualifications,and large groups get a value of 57.895 with high effectiveness qualifications. It can be concluded thatmoodle-based e-learning media is able to improve the learning outcomes of students in class VIII oddsemester of the 2024/2025 academic year at SMP Negeri 1 Ubud.